PHYSICAL ACTIVITY BEFORE DISEASE ONSET AND ITS IMPACT ON THE RISK AND CLINICAL SEVERITY OF RHEUMATOID ARTHRITIS – A NARRATIVE LITERATURE REVIEW - Katarzyna Maria Turek; Katarzyna Adrianna Tryniecka; Weronika Worosz; Alicja Zań; Diana Wisz; Filip Maciej Huzarski (International Journal of Innovative Technologies in Social Science, 2025)
Background: Rheumatoid arthritis (RA) is a chronic, systemic connective tissue disease of immunological origin and unknown etiology, characterized by nonspecific symmetric joint inflammation, extra-articular manifestations, and systemic symptoms, ultimately leading to progressive joint destruction, disability, and premature death. The disease can be classified as seropositive or seronegative depending on the presence or absence of autoantibodies in the serum, such as IgM rheumatoid factor and/or anti-citrullinated peptide antibodies (ACPA) [1]. Increasing evidence suggests that environmental factors, including lifestyle and physical activity (PA), may influence both the risk of developing RA and the clinical course of the disease [2–4]. Aim: Assessment of the impact of physical activity undertaken prior to disease onset on the risk of developing rheumatoid arthritis and on the severity of symptoms at diagnosis. Objective: To review the literature on whether PA prior to RA onset affects disease risk and severity at diagnosis. Material and methods: A literature review was conducted using the PubMed, Scopus, and Web of Science databases, covering the years 2000–2025, with the following keywords:”Rheumatoid Arthritis, ”“Physical Activity, ”“Risk, ”“Disease Severity.” The review included cohort studies, cross-sectional studies, meta-analyses, and systematic reviews. Results: A higher level of recreational physical activity during leisure time prior to disease onset is associated with a 20–35% reduction in the risk of developing RA [5–7], as well as with a milder disease course at diagnosis [8]. In contrast, high levels of occupational physical activity increase the risk of RA [9]. The protective mechanisms against disease development include modulation of the immune response, reduction of systemic inflammation, and improvement of metabolic profile [10–12]. Conclusions: Regular recreational physical activity may represent an important component of primary prevention of rheumatoid arthritis. Further prospective studies with objective measurements of physical activity are warranted.